A normal electro-oculography in a family affected by best disease with a novel spontaneous mutation of the BEST1 gene. Issue 11 (14th August 2008) - Testa, F; Rossi, S; Passerini, I; Sodi, A; Di Iorio, V; Interlandi, E; Corte, M Della; Menchini, U; Rinaldi, E; Torricelli, F; Simonelli, F
Abstract : Aims: To describe clinical and genetic findings in an Italian family affected by Best disease. Methods: Five related patients underwent a complete ophthalmological assessment; genetic testing was performed by single-strand conformation polymorphism analysis and direct sequencing of the BEST1 gene. Results: In three of five family members, the sequence analysis of the BEST1 gene revealed a single Phe-to-Leu transition at nucleotide 305 associated with clinical evidence of Best disease. Surprisingly, the electro-oculogram was normal in all affected patients. Conclusion: This study reveals a de novo mutation in the BEST1 gene never described before, sustaining the autosomal-dominant pattern of inheritance of the disease. Clinical evaluation showed phenotypic variability between affected members. In addition, these data suggest that a normal electro-oculography (EOG) does not rule out a diagnosis of Best disease, supporting instead the crucial role of molecular analysis.